+0  
 
0
38
1
avatar

The quadratic ax^2 + bx + c can be expressed in the form 2(x - 4)^2 + 8. When the quadratic 3ax^2 + 2bx + 3 is expressed in the form n(x - h)^2 + k, what is h?

 Oct 3, 2021
 #1
avatar+35058 
+2

2(x - 4)^2 + 8   expanded =  2x^2 -16x + 40         so a = 2 b = -16   c = 40

 

 

then   6x^2 -32x + 3     will become  ( by completing the square for 'x'      6 ( x^2 - 16/3 x) + 3

                                                                     

                                                               6 ( x- 16/6)^2    - 167  2/3        <======== take it from here

 Oct 3, 2021

21 Online Users

avatar
avatar